Victims who have done nothing or victims who have done nothing wrong: contesting blame and ‘innocent victim’ status in transitioning societies - Hearty, Kevin (The British journal of criminology, 2019)
Building on recent victimological interventions in transitional justice, this article critically examines nuanced interpretations of what an ‘innocent victim’ is in transitioning societies without any agreed legal, political or moral base position on past political violence. It suggests that the term refers to two different types of victims: victims who have done nothing that fit traditional victimological understandings of the blameless, passive ‘ideal victim’ and victims who have done nothing wrong where innocence and blame are open to fundamental political and moral contest. It concludes that the irreconcilability, looseness and adaptability of competing frameworks for understanding the past pose a core victimological disagreement surrounding victims who have done nothing wrong that even a more critically self-reflective approach by victimizers fails to resolve.